Bending analysis of laminated plate via polynomial RBF. (March 2019) - Singh, Jeeoot; Kumar, Rahul; Shukla, Vivekanand
Abstract: The present novel work deals with the investigation of bending response of laminated plate using five variable higher order shear defor-mation theory (HSDT). Governing differential equation (GDE) of the plate is acquired by energy principle. Polynomial radial basic function based on Meshfree method is used for discretizing the GDE. A MATLAB code is developed to obtain the results. Convergence and validation for the code is obtained using already published results. The effect of orthotropy and span to thickness ratio on the response of the plate is studied.